2020
DOI: 10.1002/jsfa.10557
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cultivar choice, hazelnut orchard management, and nut storage to enhance product quality and safety: an overview

Abstract: European hazelnut (Corylus avellana L.) is a major species of interest for nutritional use within the Betulaceae family and its nuts are widely used throughout the world in the chocolate, confectionery, and bakery industries. Recently its cultivation has been expanded in traditional producer countries and established in new places in the southern hemisphere, including Chile, South Africa, and Australia. Introducing hazelnut in new environments could reduce its productivity, lead the trees to experience eco‐phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 154 publications
(162 reference statements)
1
62
0
2
Order By: Relevance
“…In our experiments with hazelnut TDG grown in acidic soil, the leaves of untreated, control trees had 25-28 mg kg −1 DW of B and Zn. According to technical reports, the optimal B leaf contents for reaching good fruit set and hazelnut yields are between 25 and 30 mg kg −1 DW (Silvestri et al, 2021). Similarly, other authors have discussed that optimum B concentration in hazelnut leaves should be 22-30 mg kg −1 DW for productive trees (Simşek et al, 2003), while data on the beneficial effect of Zn spraying on hazelnut leaves have been studied to a lesser extent (Alidust et al, 2020).…”
Section: Effects Of Different B and Zn Spraying Programs On Hazelnut Leavesmentioning
confidence: 99%
See 3 more Smart Citations
“…In our experiments with hazelnut TDG grown in acidic soil, the leaves of untreated, control trees had 25-28 mg kg −1 DW of B and Zn. According to technical reports, the optimal B leaf contents for reaching good fruit set and hazelnut yields are between 25 and 30 mg kg −1 DW (Silvestri et al, 2021). Similarly, other authors have discussed that optimum B concentration in hazelnut leaves should be 22-30 mg kg −1 DW for productive trees (Simşek et al, 2003), while data on the beneficial effect of Zn spraying on hazelnut leaves have been studied to a lesser extent (Alidust et al, 2020).…”
Section: Effects Of Different B and Zn Spraying Programs On Hazelnut Leavesmentioning
confidence: 99%
“…We showed that the application of spraying programs (P1, P2, and P3) increased the B and Zn concentrations in the hazelnut leaves by several folds in both B+Zn treatments compared with untreated trees and the previous reports. It should be noted that the B and Zn requirements and optimum thresholds are cultivar-specific (Alidust et al, 2020;Silvestri et al, 2021), and they should be integrated into crop management to obtain the maximal yield. Our results showed that combined spraying application of B and Zn resulted in both Zn and B accumulation in totally expanded leaves in P1 and P3 programs, while the B and Zn accumulation efficiency was lower in P2 (P ≤ 0.05).…”
Section: Effects Of Different B and Zn Spraying Programs On Hazelnut Leavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nuts are highly appreciated due to their high nutritional value and health properties deriving from their unique molecular composition that are preserved for a long period of time [14]. Considering that storage has a high impact on their self-life and preservation of their nutritional components [15], packaging conditions should also be taken into account in terms of safety quality control by monitoring BPA leaching, as well.…”
Section: Introductionmentioning
confidence: 99%